PENGARUH YOGA PRANAYAMA TERHADAP KECEMASAN PADA WANITA PREMENOPAUSE DI DESA WANASARI TABANAN - Astuti, Ni Nyoman Ferry; Putu Mastiningsih; Ni Made Risna Sumawati (Jurnal Karya Generasi Sehat, 2025)
Aging is a natural process that all humans go through. Aging in women begins with entering the climacteric period which begins at the age of 40-65 years. Premenopause usually causes symptoms such as irregular menstrual cycles, hot feelings from the chest to the face, cold sweats at night, vaginal dryness, insomnia, fatigue and depression. Efforts that can be made to reduce anxiety in premenopausal women are non-pharmacological, namely yoga pranayama. Yoga is one way of meditation to calm the mind with a personal development method that aligns the body, mind, and soul through body exercises (asana), breathing flow (pranayama) and meditation or visualization. The purpose of this study was to determine the Effect of Yoga Pranayama on Anxiety in Premenopausal Women in Wanasari Village, Tabanan. This study uses a Pre Experiment design method with a one group pretest-postest design where this study Observation was carried out twice, namely before and after the intervention was given. Data were analyzed using the Wilcoxon Test. The results of the statistical test conducted to determine the level of anxiety experienced by premenopausal women before and after being given yoga pranayama obtained a value of p = 0.000 (p <0.05) which means Ho is rejected so that it can be concluded that there is an effect of yoga pranayama on anxiety in premenopausal women in Wanasari Village, Tabanan. Based on the results of this study, it is expected that Premenopausal Women can apply Yoga Pranayama to overcome anxiety.